Spread spectrum communications using chirp signals - Springer, Andreas; Gugler, Wolfgang; Huemer, Mario; Reindl, Leonhard; Ruppel, Clemens; Weigel, Robert (IEEE/AFCEA EUROCOMM 2000. Information Systems for Enhanced Public Safety and Security, 2000)
We report on the use of broadband chirp signals for spread spectrum systems in indoor applications. The presented system concepts make use of chirp transmission and pulse compression. Different modulation schemes for the chirp signals resulting in different system performance and complexity are compared in terms of bit error rate for the AWGN channel and for frequency selective indoor radio channels. We present simulations and measurement results from demonstrator systems which use surface acoustic wave (SAW) devices for the generation and matched altering of the chirp signals. The RF and IF frequency and transmission bandwidth of the presented systems are 2.4 GHz, 348.8 MHz, and 80 MHz, respectively. Due to the processing gain of 16 dB-made possible by the use of SAW devices-and the large transmission bandwidth the system is insensitive against frequency selective fading, CW interference and noise
elib2cris::1512001600,springer2000
Keywords: System performance; Surface acoustic waves; Spread spectrum communication; RF signals; Chirp modulation; Pulse compression methods; Bit error rate; Bandwidth; AWGN channels